1988
DOI: 10.1002/pd.1970080802
|View full text |Cite
|
Sign up to set email alerts
|

Umbilical cord pseudocyst in trisomy 18

Abstract: Prenatal diagnosis of cord defects by means of ultrasound examination is possible and highly accurate. Although this is a rare pathological finding, we report two cases in which umbilical cord pseudocysts were associated with trisomy 18. These observations underscore the need of umbilical blood sampling for establishing the karyotype in fetuses with such umbilical cord anomalies and the importance of careful examination of placentas and infants born with such defects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0
1

Year Published

1996
1996
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 20 publications
1
22
0
1
Order By: Relevance
“…Umbilical cord cysts or pseudocysts have been reported most commonly in association with trisomy 18 [25][26][27] or trisomy 13 28 . Smith et al 29 reported a high incidence of chromosomal or structural anomalies in fetuses with umbilical cord cysts (18 of 23 cases).…”
Section: Cystic Masses Of the Umbilical Cordmentioning
confidence: 99%
See 1 more Smart Citation
“…Umbilical cord cysts or pseudocysts have been reported most commonly in association with trisomy 18 [25][26][27] or trisomy 13 28 . Smith et al 29 reported a high incidence of chromosomal or structural anomalies in fetuses with umbilical cord cysts (18 of 23 cases).…”
Section: Cystic Masses Of the Umbilical Cordmentioning
confidence: 99%
“…Compared to true cysts, on histologic examination pseudocysts show absence of the epithelial lining. Prenatal differentiation between a true umbilical cyst and a pseudocyst on ultrasound is neither possible nor important, as pseudocysts were also associated with fetal abnormalities 25,26 . Although umbilical cord cysts may be found as a normal variant in pregnancy, a meticulous search for other structural malformations is indicated in these cases (Figure 4).…”
Section: Cystic Masses Of the Umbilical Cordmentioning
confidence: 99%
“…Several recent reports indicated that umbilical cord pseudocysts occur very frequently in fetuses with aneuploidy, especially with trisomy 18 [5][6][7][8], suggesting that their ultrasonographic detection may be of great help in the prenatal diagnosis of this disorder [5][6][7][8]. In this report, we present a case in which a fetus found to have umbilical cord pseudocysts by ultrasonography was confirmed to have trisomy 18 by karyotyping.…”
Section: Introductionmentioning
confidence: 78%
“…The present study is focused on umbilical cord cyst which has been associated to fetal anomalies and aneuploidies since 1988 in a study developed by Jauniaux et al (6) . Correlation between umbilical cord cysts and anomalies was found in up to 50% of cases, particularly in findings occurred at the second and third trimesters of gestation.…”
Section: 34)mentioning
confidence: 99%